2021
DOI: 10.1519/ssc.0000000000000666
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Functional Training to Improve Front Push Kick Technique, Speed, and Net Force Production

Abstract: Kicking is an essential skill for combat athletes and military personnel. Therefore, the aim of this article is to present evidence-based training principles to achieve beneficial changes in technique and performance through functional training. The profile of subelite and elite kickers is presented and is used as a foundation for exercise prescription in both populations. The article emphasizes the importance of combining both functional training with a core emphasis and traditional general strength preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The latter aspect is critical and creates a substantial obstacle because competitors frequently compete at their lightest feasible body mass to battle against opponents of lesser mass (26). Research analyzing sport-specific kinematics of kicks (10,27) has enhanced coaches ability to identify the most effective exercises to generate increased force output, improving performance, compared with traditional training methods (25).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The latter aspect is critical and creates a substantial obstacle because competitors frequently compete at their lightest feasible body mass to battle against opponents of lesser mass (26). Research analyzing sport-specific kinematics of kicks (10,27) has enhanced coaches ability to identify the most effective exercises to generate increased force output, improving performance, compared with traditional training methods (25).…”
Section: Introductionmentioning
confidence: 99%
“…The Teep kick (front push kick) also has similar efficacy; being one of the most used techniques in Muay Thai for attacking and countering attacks from the opponent, showing benefits from increasing competitors kicking performance impact power (14,19,22). Vagner et al (27) identified the Teep kick to be highly effective in close quarter combat, and the need for increased destructive impact was key to successful performances.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations